Methods for obtaining reliable and reproducible results in studies of Candida biofilms formed in vitro - Costa, Anna C. B. P.; Pereira, Cristiane A.; Freire, Fernanda; Junqueira, Juliana Campos [UNESP]; Jorge, Antonio O. C. (Wiley, 2013)
Biofilm formation is one of the most important attributes for virulence in Candida species and contributes to increased resistance to antifungal drugs and host immune mechanisms. These features have led to the development of several methodologies to reproduce a sessile community in vitro that can be used to study the development of a biofilm, its interaction with other microorganisms and the environment, and its susceptibility to available antifungal agents and also to search for new therapy strategies. The purpose of this review is to describe the most commonly used methods to study Candida biofilms in vitro, to discuss the benefits and limitations of the different methods to induce biofilm formation, and to analyse the architecture, viability and growth kinetics of Candida biofilms. © 2013 Blackwell Verlag GmbH.
Keywords: Biofilm; Candida spp.; Evaluating biofilms; Methods for biofilm formation; Strategies against biofilms